Complications of laparoscopic cholecystectomy: an analysis of 1,695 laparoscopic operations - Jatothu, Dasharadha; Sade, Rajkumar; Sade, Kirthana; Taruni, .; Pyadala, Nagababu (International Surgery Journal, 2017)
Background: Laparoscopic cholecystectomy (LCs) is the gold standard method to treat gallstone disease. But there are some complications which occur frequently as compared to open cholecystectomy. Methods: The prospective study was conducted in the Department of Surgery, Kamineni Institute of Medical Sciences, Telengana during the period of 2 years; March 2015 to February 2017. A total of 1,695 laparoscopic cholecystectomy cases were included in this study. Several treatment options such as, conservative treatment, minimally invasive treatment and open surgery was performed based on the severity of the disease. Results: Majority of patients were female (83.9%) and most common age group affected was above 40 years. Intra-operative and post-operative complication occurred in 4.5% and 1.9% patients respectively. Majority complications were treated by conservative treatment and minimally invasive treatment. So, in conclusion, we can use conservative and minimally invasive treatment to manage the complications from laparoscopic cholecystectomy. Conclusions: Conservative treatment options and minimally invasive treatment was more efficient to overcome the post-operative complication of laparoscopic cholecystectomy.